2012
DOI: 10.1158/1078-0432.ccr-11-1813
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Serotonin Receptors in Human Hepatocellular Cancer

Abstract: Purpose: Serotonin is a well-known neurotransmitter and vasoactive substance. Recent research indicates that serotonin contributes to liver regeneration and promotes tumor growth of human hepatocellular cancer. The aim of this study is to investigate the expression of serotonin receptors in hepatocellular cancer and analyze their potential as a cytotoxic target.Experimental Design: Using a tissue microarray and immunohistochemistry, we analyzed the expression of serotonin receptors in the liver from 176 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
53
2
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 36 publications
2
53
2
4
Order By: Relevance
“…In prostate cancer, these growth factors act on the adjacent (exocrine) tumor cells to enhance tumor growth, differentiation and angiogenesis, the events that lead to a poor prognosis [18], [70]. Recently, 5-HT 1B receptors were associated with an increased proliferation index, correlated with the size of the tumor in hepatocellular cancer patients [71], and were shown to play a potential role in colorectal cancer [69]. Since we showed here that the 5-HT 1B and 5-HT 1D receptors are highly over-expressed in PaCa cells, we tried to explore the etiological associations between its expression and PaCa progression.…”
Section: Discussionmentioning
confidence: 99%
“…In prostate cancer, these growth factors act on the adjacent (exocrine) tumor cells to enhance tumor growth, differentiation and angiogenesis, the events that lead to a poor prognosis [18], [70]. Recently, 5-HT 1B receptors were associated with an increased proliferation index, correlated with the size of the tumor in hepatocellular cancer patients [71], and were shown to play a potential role in colorectal cancer [69]. Since we showed here that the 5-HT 1B and 5-HT 1D receptors are highly over-expressed in PaCa cells, we tried to explore the etiological associations between its expression and PaCa progression.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, our data showed that pimozide decreased IL6-mediated STAT3 phosphorylation and could reverse cancer stem-like cell phenotypes induced by IL-6 addition in HCC cells, further suggesting that pimozide may be a potential agent for treating HCC cells by inhibiting STAT3 signaling and suppressing cancer stem-like cell maintenance. Besides, since pimozide is a well-known antagonist of serotonin 5-hydroxytryptamine receptor 7 (5HT7), which was overexpressed in human hepatocellular cancer (Data not shown, [49]), whether 5HT7 expression is associated with STAT3 activation in HCC cells is required to investigated in future.…”
Section: Discussionmentioning
confidence: 99%
“…26) Liang et al showed that serotonin was involved in tumorigenesis and induced a pro-proliferative effect in HCC cells via upregulation of expression of FOXO3a (a member of class O of the forkhead box family of transcription factors). 27) On the other hand, some reports indicated that serotonin reuptake transporter did not exist on liver tissue.…”
Section: Discussionmentioning
confidence: 99%